The effect of cognitive behavioral counseling on anxiety and worry level of women with intermediate risk during first trimester screening for down syndrome: a randomized controlled trial: a randomized controlled trial - Roghieh Kharaghani; Farhaneh Vaezi; Mohsen Dadashi; Leila Rastegari; Azam Maleki (BMC, 2023)
Abstract Background Anxiety related to prenatal screening programs negatively affects maternal and child health. Objective The study aimed to determine the effect of Cognitive Behavioral Counseling on the anxiety and worry levels of women with intermediate risk during first-trimester screening for Down Syndrome. Methods The study was a randomized controlled trial conducted on 52 pregnant women with intermediate risk (1: 51 − 1:1500) during first-trimester screening for Down Syndrome and without additional structural anomalies that referred to three cities of Zanjan province in 2021. The eligible women were randomly assigned to intervention and control groups, with a block size of four. The intervention group received CBC in four sessions of 120 min two times a week by phone. Data were collected using Vandenberg Anxiety Questionnaire, and Cambridge Worry Questionnaire in three phases baseline, after the intervention, and 6 weeks follow-ups. Data were analyzed using independent t-test, chi-square, and repeated measures ANOVA at a 95% confidence level. (P < 0.05). Results In the counselling group, the mean (SD) of a total score of anxiety before the intervention was 67.11 (20.68) which decreased to 32.50 (13.58) in six weeks after the intervention. Furthermore, the mean (SD) of a total score of worry before the intervention was 56.19 (16.76) which decreased to 32.96 (8.89) six weeks after the intervention. Based on the repeated measures ANOVA test, the mean total score of anxiety and worry were statistically significant 6 weeks after the intervention compared with the control group(p < 0.001). Conclusion Based on the study results, CBC can reduce the anxiety and worry levels of women with intermediate risk during first trimester screening for Down Syndrome. Trial registration The study was registered at the Iranian Registry of Clinical Trials website under the code IRCT20160608028352N8, ( https://en.irct.ir/trial/49998 ). The first trial registration date was (29/08/2020).